Validation and cross-cultural adaptation of treatment satisfaction questionnaire for medication version 2 among older adult patients in Malaysia: a psychometric testing study - Mohammad Yunus, Mohammad Adam Al Haqimy; Akkawi, Muhammad Eid (Elsevier, 2025)
Objectives: To assess the full psychometric testing of the translated Malay version of Treatment Satisfaction Questionnaire for Medication version 2 (TSQM v.2)